Representações sociais de policiais militares, sobre educação a distância no âmbito da rede EaD/SENASP - Sousa, Lourdes Losane Rocha de (2012)
Distance education has expanded significantly in various training areas. Within the corporate education of public safety professionals to network distance education at the National Secretariat of Public Security (EAD / SENASP), has been developing national continuing education of police officers, firefighters, police officers, municipal guards, through the virtual classroom. What are the social representations of the agent of public safety in relation to vocational training at a distance? The mode of distance education is a significant element in the process of professional training of public safety? What are the consequences of courses of Network EAD / SENASP in everyday practice and sociopolitical relations of the Military Police? From this context emerged the research study that aimed to identify the social representations of the military police on distance within the network EAD / SENASP, trying to identify the contributions of the courses offered for the execution of police activity. The theoretical underpinning of the study took place from the theory of social representations, as Moscovici (1978), Jodelet (2001), Sa (2004), Doise (2002). As a methodology, we conducted a qualitative research case study, with military police, soldiers, more specifically, in the city of Teresina-PI. The data collection instruments used were semi-structured questionnaire of open and closed questions. The sample consisted of 95 soldiers in the first stage and 11 in the second. The collected data were transcribed, categorized and analyzed using the technique of content analysis (Bardin, 1979). From the thematic content analysis it was found that the representations constructed by the group studied in relation to distance education is related to 'training' and 'opportunity', these representations that show the significance and meanings that the training has to exercise activity of these professionals and their ramifications in the current institutional setting and social. On the other hand, points to the opportunity to network as a space for training, advancement, innovation, evolution, study with convenience, flexibility, interaction / relationship with other institutions (Civil Police, Fire Brigade) and officers from other states. The contributions to the practice of police activity reveals significant contributions in the professional, personal, institutional. At the end, it was found that the distance from which the officers are students, has a practical meaning of training focused actions contributing to daily work of state agents, against the discourses that are aired on the effectiveness of distance education mode . Weak points in the network also were revealed indicating that need to be reviewed, discussed and modified (system evaluation, selection of tutors, monitoring the frequency of the virtual students) at the same time signaled the need for planning and implementing a state policy continuing education of these professionals.